Barriers and Effective Strategies for Stakeholder Engagement in Inclusive and Language Education: Sustainable Development Goals (SDGs) Perspective - Usmanovna, Kodirova Feruzakhon; Sadikovna, Rakhimova Khurshidakhon; Sobirkhonovna, Makhmudova Madinakhon; Rakhimovna, Teshaboeva Feruza; Jorakozievich, Melikoziev Dadakozi; Sobirjonkizi, Usmonova Mahliyo (Universitas Negeri Makassar, 2025)
This study aims to identify the barriers limiting stakeholder participation in inclusive and language education, and to develop strategies aligned with the Sustainable Development Goals (SDGs). Using visual-adaptive questionnaires, interviews, and case studies across three regions in Uzbekistan, the study explored awareness, collaboration, and infrastructure-related challenges. Results revealed that most teachers and parents had only a partial understanding of inclusive education, and students lacked methodological resources. Effective practices (such as training sessions, collaborative teams, and targeted communication) were implemented to improve engagement. These strategies proved effective because they addressed both structural and perceptual gaps, especially in supporting language development and inclusive teaching. The research highlights that coordinated and inclusive stakeholder engagement contributes significantly to educational equity. It also reinforces the role of inclusive and language education in promoting social justice and lifelong learning, consistent with SDG 4 on quality education and SDG 10 on reducing inequalities.